Pedagogical strategies in the training of agricultural engineers - Torres-Martínez, Francisco Javier; Barraza-Álvarez, Fernando Vicente; Benavides-Benavides, Orlando (Revista de Ciencias Agrícolas, 2025)
Studies on pedagogical strategies in agricultural higher education programs in Colombia are limited; hence, the need to identify the pedagogical strategies used by teachers in the training of agricultural engineers at the Faculty of Agricultural Sciences of the University of Nariño. To do so, information on the 54 subjects of the study plan was analyzed in the form "Thematic Programming by Subject" prepared by the teachers, and descriptive statistics were applied with a deductive approach. The investigation allowed the identification of the following variables: first, pedagogical strategies for knowledge transfer; second, forms of evaluation; third, origin of the bibliography recommended by teachers. The predominant strategy in the training of agricultural engineers is identified with the traditional paradigm in 36 subjects (66.7%), which correspond to the technical disciplines of the curriculum, and where the practical instruction of know-how and field research predominate. In addition, the close relationship between the programmatic contents and the development of competences in the practical field is confirmed. All the faculty in their pedagogical work still resort to the master class, a situation that demonstrates the prevalence of behavioral pedagogical strategies; likewise, most courses favor mixed evaluation; meanwhile, the individual evaluation is applied to a lesser extent, and most professors recommend bibliographical sources of foreign origin. The results constitute valuable information for the formulation of strategies aimed at strengthening the teaching-learning processes and improving the quality of Higher Education.